Risk Management Disclosures: An Investigation Using Risk Management Committee as a Moderating Variable (Jurnal Dinamika Akuntansi, 2021)
Purpose: The objective of this study is to investigate the effect of firm size, board of commissioners, independent commissioners, and auditor reputation on risk management disclosure by using risk management committee as a moderating variable.Method: The population of this research was manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The sample selection was carried out using the purposive sampling method and obtained 189 units of analysis. Hypothesis testing was carried out using descriptive statistical analysis methods and moderated regression analysis (MRA) with interaction testing.Findings: The results of this study indicated that firm size and board of commissioners have a significant positive effect on risk management disclosure, while independent commissioners and auditor reputation do not affect risk management disclosure. The risk management committee weakens the effect between the board of commissioners, the independent commissioner, and auditor reputation on risk management disclosures, while the risk management committee is unable to moderate the effect of firm size on risk management disclosures.Novelty: This is the first study that include a risk management committee as a moderating variable in the research model. The existence of RMC is expected to strengthen the company's risk mitigation including its disclosure.